An Image of Korean Women during the Japanese Occupation of the Peninsula, as It Emerges from Literary Masterpieces - Buja, Elena (Universitatea Sapientia din municipiul Cluj-Napoca, 2021)
This paper aims to offer a picture of the darkest period in the history of the Korean women, namely that of the Japanese colonial rule (1910-1945). The only advantage Korean women enjoyed as a result of their country's annexation to Japan was access to institutional education, even if this was done in Japanese and from Japanese course books. But this came with a price: many of the Korean teenaged females were turned into comfort women (sex-slaves) for the Japanese soldiers before and during the Pacific War. Not only did these girls lose their youth, but they also lost their national and personal identity, as they were forced to change their Korean names into Japanese ones and to speak Japanese. To build the image of the fate of the Korean women during this bleak period, the research method I have used is a simplified version of content analysis, "an analysis of the content of communication" (Baker 1994, 267). I have explored the content of fragments from a couple of novels authored by Korean or American-Korean authors, which cover the historical events in the peninsula leading to the end of WWII (Keller's Comfort Woman (2019) and Bracht's White Chrysanthemum (2018), to mention just a few) and which are focused on the topic of comfort women, 2 i .e. young women that were sexually exploited by the Japanese military. The results of the analysis indicate that many of the surviving victims became "unpersons" and led a life of solitude and misery until their death .